Liver fibrosis affects the targeting properties of drug delivery systems to macrophage subsets in vivo. (June 2019) - Ergen, Can; Niemietz, Patricia Maria; Heymann, Felix; Baues, Maike; Gremse, Felix; Pola, Robert; van Bloois, Louis; Storm, Gert; Kiessling, Fabian; Trautwein, Christian; Luedde, Tom; Lammers, Twan; et al.
Abstract: Myeloid immune cells promote inflammation and fibrosis in chronic liver diseases. Drug delivery systems, such as polymers, liposomes and microbubbles, efficiently target myeloid cells in healthy liver, but their targeting properties in hepatic fibrosis remain elusive. We therefore studied the biodistribution of three intravenously injected carrier material, i.e. 10 nm poly(N-(2-hydroxypropyl)methacrylamide) polymers, 100 nm PEGylated liposomes and 2000 nm poly(butyl cyanoacrylate) microbubbles, in two fibrosis models in immunocompetent mice. While whole-body imaging confirmed preferential hepatic uptake even after induction of liver fibrosis, flow cytometry and immunofluorescence analysis revealed markedly decreased carrier uptake by liver macrophage subsets in fibrosis, particularly for microbubbles and polymers. Importantly, carrier uptake co-localized with immune infiltrates in fibrotic livers, corroborating the intrinsic ability of the carriers to target myeloid cells in areas of inflammation. Of the tested carrier systems liposomes had the highest uptake efficiency among hepatic myeloid cells, but the lowest specificity for cellular subsets. Hepatic fibrosis affected carrier uptake in liver and partially in spleen, but not in other tissues (blood, bone marrow, lung, kidney). In conclusion, while drug carrier systems target distinct myeloid cell populations in diseased and healthy livers, hepatic fibrosis profoundly affects their targeting efficiency, supporting the need to adapt nanomedicine-based approaches in chronic liver disease.